Limited Domain of Fair Balance in Legal Order - Trajković, Marko; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Abstract: The limited scope of justice and fair balance in the legal order is a direct result of the inability to precisely define what justice is, as well as the inability to avoid the pitfalls of empty linguistic formulas. This danger is even more pronounced when these empty formulas appear in regulations with an imperative character, especially in the domain of criminal law. In this way, a legal regulation can fix an evil that can later be justified by the same legal regulation. This is how we came to complete legal systems that can be called evil in themselves. The crime that resulted from the disturbed balance was also the cause of indifference to individual suffering. Then both the legislation and the judiciary failed and remained silent in the face of crimes, and thus the human balance was disturbed. This disturbed balance was the cause of new crimes, before which conscience recoiled and left a very good breeding ground for crime. From this it can be seen that silence in the face of crime and its legalization has never led to good. Good has not disappeared completely, but rather has been suppressed by the force of violence and remained on the margins of society, which could no longer distinguish between good and evil.